A strategy for the promotion of renewable energy for cleaner production in G7 economies: By means of economic and institutional progress - Huihui, Wang; Alharthi, Majed; Ozturk, Ilhan; Sharif, Arshian; Hanif, Imran; Dong, Xiaohong (Journal of cleaner production, 2024)
Based on the experience of G-7 economies, the present study provides a strategy for other developed and developing nations to expedite the transition process from nonrenewable to clean renewable energy for cleaner production. To establish an empirical framework, data of G-7 democracies considered from 1995 to 2020 and employed the Augmented Mean Group model to expose the short-run and long-run influence of institutional quality and quality of democracy to switch from nonrenewable to renewable energy trajectory. The pace of transition is measured in terms of the ratio of renewable energy in the total energy mix, and a higher ratio indicates a greater share of renewable energy in total energy produced from different nonrenewable sources such as Oil, coal, and gas. The findings indicate that institutional quality and strong democratic governments are more active in developing renewable energy infrastructure as compared to governments operating with weak institutions and poor quality of democracy. The coefficient of the Institutional quality variable is greater than the variable of democracy quality, these findings infer that strong institutions are an inevitable and crucial factor in making a swift transition from nonrenewable to renewable energy production in G-7 democracies. •The quality of democracy plays an important role to promote renewable energy policies.•The quality of Institutions helps to implement renewable energy policies in G-7 countries.•High oil prices discourage the use of fossil fuels and encourage investment in renewable energy projects.•The addition in national income also improves the share of renewable energy in the total energy mix.•The pace of transition from nonrenewable to renewables can improve through strong democratic governments.